Pengaruh Citra Merek, E-WOM dan Customer Rating terhadap Keputusan Pembelian Skincare Glad2Glow di Kota Batam - Syahrinda Fina; Inda Sukati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid growth of digital platforms has significantly transformed consumer behavior in the skincare industry, particularly in urban areas such as Batam City. Consumers increasingly rely on brand perception, online information, and collective evaluations before making purchasing decisions. This study aims to examine the influence of brand image, electronic word of mouth (E-WOM), and customer rating on purchasing decisions of Glad2Glow skincare products in Batam City. A quantitative explanatory approach was employed using purposive sampling, involving 100 respondents who met specific criteria as active skincare consumers. Data were collected through structured questionnaires and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that brand image, E-WOM, and customer rating each have a positive and statistically significant effect on purchasing decisions. Among the three variables, customer rating demonstrates the strongest influence, followed by brand image and E-WOM. Simultaneously, the three independent variables show a high explanatory power in predicting consumer purchasing decisions. These findings highlight the importance of strengthening brand perception, managing digital consumer communication, and maintaining credible customer ratings to enhance purchasing decisions in the competitive skincare market.